1989
DOI: 10.2166/wst.1989.0027
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality in Residential Tidal Canals

Abstract: Monitoring of water quality in residential tidal canals in Queensland has been carried out since 1974. Some recent data from four separate canal systems and their source waters is presented. Source water quality was generally good and this high quality was maintained in surface waters throughout these systems. Stratification of the water column in poorly flushed canal branches led to periodic deterioration in bottom water quality but this never resulted in significant management problems. Based on the Queensla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…Their construction has increased considerably worldwide in the past decades (Waltham & Connolly 2011). It has been shown that these modified estuaries receive high loads of land-derived nutrients, support high primary production rates, high OM deposition, and consequently promote changes in macrofauna structure (Cook et al 2007;Cosser 1989;Lemckert 2006;Maxted et al 1997;Morton 1989;Moss 1989). Accordingly, a number of concerns have arisen from the increase in the construction of these developments (Smith et al 1995); however, the potential threats they pose to coastal ecosystem nutrient cycling have been poorly addressed.…”
Section: Human Impacts In Estuariesmentioning
confidence: 99%
See 4 more Smart Citations
“…Their construction has increased considerably worldwide in the past decades (Waltham & Connolly 2011). It has been shown that these modified estuaries receive high loads of land-derived nutrients, support high primary production rates, high OM deposition, and consequently promote changes in macrofauna structure (Cook et al 2007;Cosser 1989;Lemckert 2006;Maxted et al 1997;Morton 1989;Moss 1989). Accordingly, a number of concerns have arisen from the increase in the construction of these developments (Smith et al 1995); however, the potential threats they pose to coastal ecosystem nutrient cycling have been poorly addressed.…”
Section: Human Impacts In Estuariesmentioning
confidence: 99%
“…Another feature of these artificial waterways have a single or very few outlets connecting them to the outer estuary or open waters. Their design is typically long, narrow and deeper than the water source (Lindall & Trent 1976;Maxted et al 1997;Moss 1989). As a result, the tidal exchange with the water source is diminished, causing poor flushing and low flow of water.…”
Section: Canal Estates Systemsmentioning
confidence: 99%
See 3 more Smart Citations